Peran Penulis Naskah Dalam Pembuatan Program Feature Kuliner “Rasa Nusantara” Edisi Warung Mjs - Annisa Cikal Kartika Putri Madya; Muhammad Darwinsyah (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
Abstract - Indonesia can be said to be a place rich in culinary delights because there are various types of cuisine in each region, both in the form of heavy meals and snacks. The progress of increasingly modern times has more or less influenced the decline in the popularity of several typical Indonesian foods. Television must develop more creativity in Indonesian culinary feature programs. Therefore, a culinary feature program entitled "Rasa Nusantara" Warung MJS edition was created. This feature program will provide information about unique culinary locations in the archipelago with an exploration of the themes of these places which are characteristic. This program is not only informative, but has the impact of inviting the audience to learn more about the variety of typical Indonesian foods. In this program, the creator of the work acts as a script writer, where his duties involve the ability to develop an idea into a script, create a treatment, create a list of questions for interviewing sources, and compose the script. The general benefits include adding to Indonesian culinary tourism shows, as well as providing alternative entertainment for viewers of this program. The creator of the work hopes that with this culinary feature program the younger generation will participate in preserving Indonesia's culinary riches. Keywords: program feature, culinary, scriptwriter